Features of diagnostics for patients with symptomatic tunneled coronary arteries - O. Gogayeva (Ukrainian Journal of Cardiovascular Surgery, 2018)
Given article is devoted to location anomaly of coronary arteries so called tunneled coronary arteries (TCA). Based on the world’s biggest experience of 347 symptomatic patients, author performed fundamental analysis and practiced the most effective methods for verification of patients with such an anomaly. The main reason for the hospitalization of patients was angina pectoris, 54.1% of them had myocardial infarction in anamnesis, 95.6% of patients had psychosomatic disorders; dyspnea attacks had 67.1% of them. It is important to note that one of the clinical features of TCA is nitrates intolerance, due to an increase in systolic compression of tunneled segment of the coronary artery (CA). The new high peculiar features of ECG were detected for the first time and that allowed to improve an angiographic verification of TCA. Transient change in the depth of inverted T wave in left precordial leads on ECG is due to the dynamic nature of compression of the intramural CA. The typical angiographic symptom of TCA – «milking-effect» was observed in 92% of patients. In 96.8% of cases myocardial bridge was settled down at the LAD, with average systolic compression 70%, average length of the tunneled segment was 28 mm. Implementation in practice provocative test with isosorbide dinitrate during angiography has improved visualization of systolic compression of coronary artery (CA) in 75.7 % cases. Also we found an indirect sign of myocardial bridge in the form of hypokinesis of the anterior wall and apex of the left ventricle in 94 (27.08%) patients. The specific “half-moon” phenomenon on IVUS was met in 82.9% of cases.